IDENTIFICATION OF BENEFICIARIES REQUIREMENTS ON ON-LINE TRADE - SPÎNACHII Elena; MALCOCI Marina; PÎRVAN Evgheni; GHELBET Angela; MATRAN Cristian (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2019)
The development of e-commerce and the emergence of virtual enterprises have led to the possibility of transforming traditional businesses into virtual enterprises for which the IT system no longer constitutes a complementary element, but even the foundation of the organizational structure. According to the concept of marketing, the most important stakeholders in an organization are customers. A questionnaire was developed to carry out the case study. It wants to identify whether the population purchases online products and whether they are willing to buy online footwear from the Republic of Moldova. To conduct the survey, the specialized website www.isondaje.ro was accessed. The survey was conducted nationwide, and the data collection method applied is on-line. The study was conducted on a sample of 60 people, of which 75% were feminine and 25% male, aged 15-53 and living in rura and urban. It is certain that the data obtained identified that respondents were actively involved in e-commerce. The advantage of this finding may also be an opportunity for the native shoe manufacturer, which is based on an intelligent approach to sales strategies and the development of distribution channels, as the market share to which it should tend to not be the maximum but the optimal one. The direction of the domestic shoe manufacturer's e-commerce must motivate the management of the enterprise to marketing and innovation, to change, where the client-producer relationship is not just a fictitious image but also a surplus.